Students’ Perceptions of Workplace Robots in the Republic of Serbia - Jelena Lukić Nikolić (Management)
Research Question: The key research question is what the key positive and negative perceptions of students from the Republic of Serbia regarding workplace robots are. Motivation: Academics, practitioners, and decision-makers are more and more interested in the impact of new technological solutions in the field of robotics on organizations and their functioning. Ongoing technological advancements have accelerated the adoption and use of robots in the workplace. As a result, organizations that plan to introduce robots should consider all effects on employees, both positive and negative. Idea: The main idea is to examine and analyse the perceptions and attitudes of students from the Republic of Serbia regarding robots at the workplace. The results of this study regarding students' perceptions and attitudes towards robots in the workplace are crucial for the future of work and job design. Data: Data were collected via online questionnaire consisting of five profile questions and 13 statements organized in two five-point Likert scales. From January to March 2023, the questionnaire was completed by 164 students from the Republic of Serbia. Tools: The collected answers were analysed using the Statistical Package for Social Sciences – SPSS, version 21.0. (Armonk, NY: IBM Corporation). The Cronbach's Alpha coefficient, Kolmogorov-Smirnov test, descriptive statistics, student t-test and one-way ANOVA test was used for data analysis. Findings: Research results showed that most respondents believe that robots can do dangerous jobs that humans cannot, that robots can free humans from routine and monotonous jobs, and that humans will have more time for creative tasks. Robots in the workplace, on the other hand, will have some negative consequences. Many respondents agree that working with robots without people would make them feel lonely; robots would not know how to react in some unexpected circumstances; and they are not as flexible and mobile as humans. Contribution: The findings of this study could make a significant contribution to a better understanding of students’ attitudes towards robots in the workplace and they may help decision makers, employers, leaders, and managers on how to increase workplace acceptance of robots.